2021
DOI: 10.3390/ijms22115705
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress as a Possible Target in the Treatment of Toxoplasmosis: Perspectives and Ambiguities

Abstract: Toxoplasma gondii is an apicomplexan parasite causing toxoplasmosis, a common disease, which is most typically asymptomatic. However, toxoplasmosis can be severe and even fatal in immunocompromised patients and fetuses. Available treatment options are limited, so there is a strong impetus to develop novel therapeutics. This review focuses on the role of oxidative stress in the pathophysiology and treatment of T. gondii infection. Chemical compounds that modify redox status can reduce the parasite viability and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 147 publications
0
38
0
1
Order By: Relevance
“…The role of this enzyme in toxoplasmosis was evident by increased parasite burdens in infected mice administered iNOS inhibitor aminoguanidine and increased susceptibility to toxoplasmosis in iNOS-deficient mice during the late phase of infection [ 16 ]. Increased NO level during toxoplasmosis is pathognomonic, which is generated to control the disease [ 108 ]. However, all strains of toxoplasmosis adopted an evading strategy to escape NO harmful effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of this enzyme in toxoplasmosis was evident by increased parasite burdens in infected mice administered iNOS inhibitor aminoguanidine and increased susceptibility to toxoplasmosis in iNOS-deficient mice during the late phase of infection [ 16 ]. Increased NO level during toxoplasmosis is pathognomonic, which is generated to control the disease [ 108 ]. However, all strains of toxoplasmosis adopted an evading strategy to escape NO harmful effect.…”
Section: Discussionmentioning
confidence: 99%
“…In the present work, a significant rise of nitric oxide level has been recorded in liver homogenate of a chronically infected group of mice sacrificed 9 wpi compared with the non-infected control subjects. This result is not surprising since Toxoplasma infection is known to induce oxidative stress in the liver of infected hosts [ 108 ]. This stressful condition is a state of imbalance between the production of reactive oxygen species (ROS) by the infected host and the antioxidant system of the invading organism [ 110 ].…”
Section: Discussionmentioning
confidence: 99%
“…LPO is recognized as an oxidative stress marker that, when elevated, can cause some biological damage such as destruction of cell membranes and release of hepatotoxicity indicator enzymes (Niki et al, 2005). During the T. gondii infection, mainly in the primary phase of diseases, tissue damage can occur due to the rise in the production of free radicals (Szewczyk-Golec et al, 2021). Here, we reported that the treatment of infected mice with RJ at the doses of 200, 400, and 600 mg/kg resulted in a significant reduction in the levels of LPO and NO (p < 0.01) whereas a significant increase (p < 0.05) in the amount of GPx and SOD was observed.…”
Section: Discussionmentioning
confidence: 99%
“…An example of such damage was described in the case of Trichomonas vaginalis infections with significant impact on cellular trans-epithelial resistance (TEER) [11]. Following infection, parasites will trigger the host NADPH oxidases to produce and release reactive oxygen species (ROS); however, eukaryotic cells are equipped with molecular mechanisms required to reduce the damaging effects of oxidation [12]. They will activate the defensive enzymes, including superoxide dismutase (SOD) [13] or catalases (CAT), to counteract the damaging effects of the oxidative burst.…”
Section: Introductionmentioning
confidence: 99%